Enhancing radiotelephony competence in aviation cadets: a quasi-experimental study on the efficacy of STEM-based learning - Ahmad Hariri; Yeti Komalasari; Minulya Eska Nugraha; Yani Yudha Wirawan (Jurnal Konseling dan Pendidikan, 2026)
This study aimed to investigate the effect of a STEM-based learning intervention on aviation cadets’ understanding of radiotelephony practices. A quantitative approach was employed using a quasi-experimental non-equivalent control group design involving 18 cadets in the experimental group (MBU 06 A), who received STEM-based learning through a radiotelephony simulation module, and 17 cadets in the control group (MBU 06 B), who received conventional instruction. Data analysis was conducted using an independent samples t-test after the assumptions of normality and homogeneity of variance were satisfied at a significance level of 0.05. The results showed that post-test scores in the experimental group were significantly higher (M = 83.17, SD = 1.95) than those in the control group (M = 69.94, SD = 1.39), with a statistically significant difference (p < .05). These findings indicate that the integration of STEM-based learning and simulation activities can enhance the effectiveness of radiotelephony instruction and better prepare aviation cadets for operational communication tasks. The novelty of this study lies in the application of a STEM-based learning framework specifically to radiotelephony training within aviation education, an area that has received limited empirical attention. This research contributes evidence that STEM-based learning is an effective pedagogical strategy for developing practical radiotelephony competence and offers valuable implications for the improvement of aviation training curricula.